2022
DOI: 10.3390/ijerph19042054
|View full text |Cite
|
Sign up to set email alerts
|

Is Injury an Occupational Hazard for Horseracing Staff?

Abstract: Occupational health is a key priority for the horseracing industry, yet little research on occupational injuries exists. This study investigated the prevalence and the effect of injury in British horseracing staff during a 12-month period. An online retrospective survey was answered by 352 participants, identifying self-reported injury prevalence, injury management practices and attitudes towards workplace injury reporting. Chi Squared tests for independence were undertaken. A total of 310 (88.1%) staff report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 102 publications
(196 reference statements)
0
18
1
Order By: Relevance
“…Stratification of our data by anatomical location demonstrates the upper limb (43.5%) being the most commonly injured, followed by the torso (21.7%) and lower limb (21.7%). While limited, there are some data on reporting of work-related injury rates among staff within the sports industry, specifically relating to equestrian racing 43 44. In contrast to our data, Cowley et al 44 identified a greater number of lower limb injuries within their staff population with an IP of 37%, while back plus chest and abdomen included 24% and upper limb were 21% of reported injuries 44.…”
Section: Discussioncontrasting
confidence: 89%
“…Stratification of our data by anatomical location demonstrates the upper limb (43.5%) being the most commonly injured, followed by the torso (21.7%) and lower limb (21.7%). While limited, there are some data on reporting of work-related injury rates among staff within the sports industry, specifically relating to equestrian racing 43 44. In contrast to our data, Cowley et al 44 identified a greater number of lower limb injuries within their staff population with an IP of 37%, while back plus chest and abdomen included 24% and upper limb were 21% of reported injuries 44.…”
Section: Discussioncontrasting
confidence: 89%
“…This is attributed to decreased enzymatic activity, lowered glycogenolysis, and an increased oxygen cost of exercise for the same output [154,[156][157][158]. However, working practices within the equestrian industry [159] and work-riding balance in amateur equestrian athletes [44] may inadvertently increase time spent in ketosis or with low CHO availability through early waking hours and time spent exercising in a fasted state. When ketosis is experimentally induced via exogenous supplementation, aspects of cognitive performance may be impaired [160,161] (we acknowledge that in clinical neurological models, ketosis may exert therapeutic effects [162,163]).…”
Section: Fatmentioning
confidence: 99%
“…Mental health can be defined as the "state of well-being in which the individual realizes his or her own abilities, can cope with the normal stresses of life, can work productively and fruitfully, and is able to make a contribution to his or her community" [4]. Concerns for racing staff mental health have already been reported; increased pressures due to a "relentless" fixture list [5][6][7], lack of work-life balance resulting in a reduced recovery time [5,6] and high rates of injury [8,9] have been identified as significant risk factors. An industry report suggested 72% of training yard staff experienced stress, anxiety, or depression in the prior 12 months [3].…”
Section: Introductionmentioning
confidence: 99%
“…Occupations with high physical and emotional pressure often have perceived assumptions that participants are physically and mentally strong [13], resilient and selfsufficient [14], and accustomed to working through pain [15], which, whilst required for the demands of the job [14], becomes problematic for mental health when those assumptions are challenged, for example due to injury [16]. Horseracing is a physically, mentally, and emotionally demanding occupation [9,17], and multiple risk factors have recently been identified that may increase the risk of injury for horseracing staff [8,9]. There is a high prevalence of injury in horseracing, with staff self-reporting an average of 3.3 injuries per annum [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation